Modeling of Multiarticular Muscles: Importance of Inclusion of Tendon—Pulley Interactions in the Finger - Lee, Sang Wook (IEEE Trans Biomed Eng, 2009)
The purpose of this study was to examine force transmission from one of the major multiarticular muscles of the finger, flexor digitorum profundus (FDP), to the index finger. Specifically, we examined whether the popular moment arm (MA)–joint torque technique of modeling muscle force transmission can accurately represent the effects of the FDP on finger movement. A dynamic finger model employing geometric MA values (model I) was compared with another model including realistic tendon force transformation mechanisms via pulley structures and joint reaction forces (model II). Finger flexion movements generated by these models were compared with those obtained from in vivo stimulation experiments. The model with the force transformation mechanisms (model II) resulted in more realistic joint spatial coordination (i.e., proximal interphalangeal > metacarpophalangeal ≥ distal interphalangeal) than the MA-based model (model I) in relation to the movement patterns evoked by stimulation. Also, the importance of the pulley structures and passive joint characteristics was confirmed in the model simulation; altering/eliminating these components significantly changed the spatial coordination of the joint angles during the resulting movements. The results of this study emphasize the functional importance of the force transformation through various biomechanical components, and suggest the importance of including these components when investigating finger motor control, such as for examining injury mechanisms or designing rehabilitation protocols.